Semiotic Narrative Analysis: Jewish Voice for Peace’s Alternative Media Narration - Syifa Azzahra; Tri Hastuti Nur Rochimah; Muhammad Raqib Mohd Sofian (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2026)
Mainstream media has huge role in constructing reality since it can build majority’s perspective. In some issues, the core encounter to challenge it is forming alternative media to resist the public opinion. This research aims to analyze the semiotic narrative in Jewish Voice for Peace's Instagram content regarding the representation of Jewish and Judaism in the context of Israel-Palestine conflict. The researcher used qualitative method with narrative analysis approach. The data were collected from feed articles related to the existing cases and analyzed using Julien Greimas model, such as Mythical Actantial and Semiotic Square. The research result showed that Jewish Voice for Peace represents Jewish and Judaism as non-Zionist identity and the advocate for Palestinian rights. Thus, this alternative media provides more critical interpretation to the audience, including the existence of Jews’ power in speaking their voice within worldwide society.